2009
DOI: 10.1186/1756-0500-2-203
|View full text |Cite
|
Sign up to set email alerts
|

Variants of ESR1, APOE, LPL and IL-6 loci in young healthy subjects: association with lipid status and obesity

Abstract: Findings: BMI was increased (>25) in 22% of young healthy subjects. Increased cholesterol values (>5.0 mmol/L) were found in 23% of subjects, LDL-C (>3.0 mmol/L) in 23%, triglycerides (>1.7 mmol/L) in 11% of subjects. We found statistically significant differences in subjects' weight (p = 0.015), BMI (p = 0.023), and waist-hip ratio (WHR) (p = 0.015) in regard to their diet type; subjects with Mediterranean diet had the lowest values compared to those on continental and mixed diet. Significant associations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
(20 reference statements)
1
8
0
Order By: Relevance
“…Sertic and colleagues reported an association between anthropometric factors including weight, BMI, and waist‐hip ratio (WHR) with diet type. Additionally, these results showed that several genetic variants (ESR‐1, LPL, and APO E) could be considered as predictive genetic risk factors for obesity‐related metabolic disorders in healthy adults . We also found that adherence to western pattern was associated with higher BMI …”
Section: Discussionsupporting
confidence: 51%
“…Sertic and colleagues reported an association between anthropometric factors including weight, BMI, and waist‐hip ratio (WHR) with diet type. Additionally, these results showed that several genetic variants (ESR‐1, LPL, and APO E) could be considered as predictive genetic risk factors for obesity‐related metabolic disorders in healthy adults . We also found that adherence to western pattern was associated with higher BMI …”
Section: Discussionsupporting
confidence: 51%
“…In this current study, there appears to be a significant increase in female lipid profile respectively across the entire ApoE genotypes with gender taken into consideration (Tables 5 , 6 ) in the studied population with the exception of TG carriers of ApoE rs429358 genotype (Table 5 ). It is reported that heredity may explain ~35–60% of variability in the plasma lipids (Weiss et al, 2006 ), which may suggest that, regardless of the genetic factors; other factors (perhaps including in vivo endocrine activities) may contribute to the gender variation of serum lipids traits in Chinese adults (Sertic et al, 2009 ). The inconsistency with our present study in comparison other reported studies might be attributed to the geographic and ethnic differences in different population studies as well as the physiological status of the participants.…”
Section: Discussionmentioning
confidence: 99%
“…APOE also plays an important role in the development of obesity and insulin resistance, which are components of MetS. Studies have also reported associations between MetS components and polymorphisms of APOE [3031]. Despite the primary role of APOE to dyslipidemia, obesity, and insulin resistance in the development of the MetS, the functional interaction of MetS with APOE protein in the lipid-lipoprotein transport system and PPARα pathway remain unclear.…”
Section: Discussionmentioning
confidence: 99%